The significance of inflammation in pathogenesis, diagnosis and treatment of atherosclerosis - Šačić Dalila; Glumac Sofija; Radojević-Škodrić Sanja (Medicinski Podmladak)
Atherosclerosis is a chronic disease whose progression starts from birth. The basic substrate of an atherosclerotic lesion is the deposition of lipids in the intima of the blood vessel, which results in gradual narrowing and impaired blood flow through the tissues. The clinical manifestations of the atherosclerotic process are numerous and they depend on the degree of narrowing and the speed of the stenosis. The most common clinical manifestations are the result of rupture of the atherosclerotic plaque, which activates the process of thrombogenesis and leads to the development of blockage of blood vessels. The most important risk factors for atherosclerosis are elevated LDL, decreased HDL, cigarette use, hypertension, type II diabetes mellitus, age, family history of cardiovascular disease in first-line relatives (men younger than 55 years, women younger than 65 years). When mild forms of atherosclerosis are observed, they generally do not have any symptoms. With advanced atherosclerosis, there are visible and noticeable symptoms that vary depending on which artery is affected by atherosclerotic process. Some of them are: chest pain - caused by atherosclerosis in the arteries of the heart, acute brain ischemia or stroke - caused by atherosclerosis in the arteries leading to the brain, difficulty walking - narrowed arteries in the legs, high blood pressure, kidney failure, erectile dysfunction in men and painful relations in women - atherosclerosis in the arteries of the genital tract. The aim of this paper is to adequately investigate and show the connection between inflammation and atherosclerosis.